Eksplorasi Peran Musik Liturgi Gereja Kharismatik dalam Membentuk Pengalaman Emosional dan Partisipasi Jemaat - Fingfing Keren Grace Wong; Nira Olyvia Purmanasari (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
Liturgical music, a central element in Charismatic church worship, is believed to evoke spiritual emotions and encourage congregational participation. This research explores the role of liturgical music in shaping the emotional experience and participation of congregations through library research methods and thematic analysis. Findings show that liturgical music plays an important role in evoking a variety of emotions, such as joy, sadness, and exaltation, as well as encouraging congregational participation through singing, dancing, and other movements. This research provides a new contribution to the understanding of the role of liturgical music in worship and its implications for the spiritual life of Charismatic church congregations.